Assessment of nanoliposomes loaded with daidzein for ameliorating diabetes in alloxan-induced mice: A promising nutraceutical approach - Negar Chalaki Rad; Ehsan Karimi; Homa Mahmoodzadeh Akherat; Ehsan Oskoueian; Mohsen Zareian (Journal of Functional Foods, 2023)
The present study synthesized and evaluated the effects of nanoliposomes loaded daidzein (NLD) in diabetic mice induced by alloxan. Five groups of Balb-c mice were treated for 5 weeks (Group 1 and 2 referred to as normal and diabetic control receiving normal feed). Group 3 and 4 were diabetic mice receiving 50 and 100 mg/kg/BW NLD respectively. Group 5, diabetic mice, received the standard drug, Metformin, 250 mg/kg/BW per day orally. Results indicated that NLD significantly (p < 0.05) improved the final body weight, triglyceride (TG), total cholesterol (TC) concentrations, low-density lipoprotein cholesterol and malondialdehyde (MDA) levels and enhanced the high-density lipoprotein. Furthermore, NLD enhanced the expression of CAT and suppressed iNOS gene in the pancreas. The mRNA expression of GLUT2 and GLUT4 also showed increase in the diabetic mice. Findings demonstrated the potential of NLD as a nutraceutical for the prevention and/or treatment of diabetes without toxic side effects.